Factores de riesgo para la displasia del desarrollo de la cadera en niños menores de 1 año de edad - Urtecho Gaitán, Iván Freddy (2017)
Determine if; Female sex, breech presentation, primiparity, macrosomia and advanced maternal age are Risk Factors for Hip Development Dysplasia in children under 1 year of age. Materials and methods: A retrospective analytical study of cases and controls was carried out. The data were taken from clinical records of patients under 1 year of age of the HRDT. The Chi square test was applied with a level of significance (p <0.05) and the strength of association with Odds Ratio (OR) and a 95% confidence interval. Results: When calculating the degree of association between the DDC variables and sex, an OR = 3.3 was obtained (p = 0.003, 95% CI 1.466-7.428), CDD and breech presentation, OR = 3.19 (p = 0.011; % 1,274-7,994), DDC and pimiparity, OR = 2,117 (p = 0.039, 95% CI 1.031-4.345) CDD and macrosomia, OR = 2.15 (p = 0.2, 95% CI 0.653-7.082) CDD and maternal age advanced, OR = 2.438 (p = 0.0361, 95% CI 1.045-5.688). Conclusion: Female sex, breech presentation, primiparity, advanced maternal age are risk factors for CDD